Effects of Childhood Experiences of Family Violence on Adult Partner Violence: A Meta‐Analytic Review. Issue 4 (December 2015) - Smith‐Marek, Erika N.; Cafferky, Bryan; Dharnidharka, Prerana; Mallory, Allen B.; Dominguez, María; High, Jessica; Stith, Sandra M.; Mendez, Marcos
Abstract : This meta‐analysis examined the association between being raised in a physically violent home and becoming an adult victim or perpetrator of physical intimate partner violence (IPV). We also explored the effects of sex of child victim and sex of parent perpetrator. In total, 124 studies, which reported 288 effect sizes measuring the association between witnessing interparental violence and/or experiencing child abuse and adult IPV, were included. Results revealed small effect sizes, with stronger effect sizes for perpetration than for victimization. The relationship between experiencing family‐of‐origin violence and subsequent IPV perpetration was significantly stronger for males than for females. The relationship between experiencing family‐of‐origin violence and subsequent IPV victimization was significantly stronger for females than for males.